2017
DOI: 10.1007/978-3-319-66179-7_75
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Multi-model Ensemble for Benign-Malignant Lung Nodule Classification on Chest CT

Abstract: The classification of benign versus malignant lung nodules using chest CT plays a pivotal role in the early detection of lung cancer and this early detection has the best chance of cure. Although deep learning is now the most successful solution for image classification problems, it requires a myriad number of training data, which are not usually readily available for most routine medical imaging applications. In this paper, we propose the transferable multi-model ensemble (TMME) algorithm to separate malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…A preliminary version of this work was presented in MICCAI 2017 [40]. In this paper, we have substantially revised and extended the original paper.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary version of this work was presented in MICCAI 2017 [40]. In this paper, we have substantially revised and extended the original paper.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Sahu et al 13 proposed a lightweight multiā€section CNN for lung nodule classification and achieved a good result in reducing memory usage. Compared with the work 14 proposed by Xie et al, it reduced memory usage by 80% and maintained an accuracy rate of 93.18%. But the phenomenon of high memory occupation still exists.…”
Section: Related Workmentioning
confidence: 82%
“…It is found that Anand et al 42 achieved the lowest accuracy in this table, because this method only use coupled textural feature to predict lung tumor. Xie et al 14 adopted transferable multiā€model for better mining features of lung nodules and the highest accuracy achieved. Our method, which combines deep visual features learned by CNN and relevant information obtained by LSTM, achieved good result using sensitivity metric while having limited data.…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al [76] proposed an agile CNN model to overcome the challenges of small-scale medical datasets and nodules. Considering the limited chest CT data, Xie et al [77] used transfer learning algorithm to separate benign and malignant pulmonary nodules. Shen et al [78] presented a multicrop CNN (MC-CNN) to automatically extract nodule salient information for the investigation of the lung nodule malignancy suspiciousness.…”
Section: Pulmonary Nodule Classificationmentioning
confidence: 99%